Effect of porosity on tensile properties of cast particle reinforced MMC - Ahmad, S. N. A. S.; Hashim, J.; Ghazali, M. I. (SAGE Publications, 2007)
The aim of this study is to investigate the effect of porosity on the tensile properties of cast discontinuous reinforced metal matrix composite (DRMMC) at room temperature. Aluminum silicon alloy reinforced with silicon carbide particles of {approx} 20 Âµm size are fabricated via conventional and modified stir casting methods. Specimens are cast at varied content of silicon carbide particles for porosity measurement and tensile test. The porosity content is measured using an image analyzer while the tensile test is conducted according to the ASTM B557 test method. A finite element method (FEM) based simulation is produced using Solidworks 2003 software to identify the effect of porosity formation at the strain areas caused by axial loading. From the evaluated findings, the porosity content increased with an increase in reinforcing silicon carbide particles. The deviation between conventional stir cast DRMMC and modified stir cast DRMMC is an average of 68%, which indicates a significant porosity reduction using the modified stir casting method. Porosity formation in conventional stir cast DRMMC is revealed to constrain the specimen to lower the tensile strength and yield stress. Based on the FEM analysis, the effect of this constraint is indicated by a high von Mises stress distribution at porosity-affected areas. The highest von Mises stress of 40.2 MPa is revealed in porosity-affected conventional stir cast DRMMC, whereas, with the minimal content of porosity, the highest von Mises stress produced in the modified stir cast DRMMC is 12.6 MPa.